تأليف الكتاب المنهجي المدرسي - Miftachul Taubah (Universitas Yudharta Pasuruan, 2019)
These members have represented a growing growth in the media, such as the press, radio and television. They also represent the interest of educational and cultural institutions in teaching the national languages ​​of foreigners. The study of foreign languages ​​is vital in our time. Many educators recommended that every child in primary school have an opportunity to teach a foreign language, a relationship to an opportunity that is already available at the secondary school level. There are a set of principles, principles, conditions and specifications that have been used in the preparation and writing of educational materials in the field of teaching Arabic in public education. We will rely on three important aspects that should be followed by any article or book to teach Arabic. These aspects are: 1) Psychological, 2) Cultural, 3) Language.